Nilai-nilai Pendidikan Karakter dalam Tradisi Lokal Solo Sebagai Upaya Peningkatan Kesadaran Sejarah bagi Generasi Muda - I Made Ratih Rosanawati; Sri Marmoah; Farida Nurhasanah (Universitas Batanghari Jambi, 2023)
The purpose of this study is 1) to describe the form of local traditions adopted by the people of Solo, 2) to describe what characters exist in the local traditions adopted by the people of Solo, and 3) to analyze the relevance of local tradition studies to efforts to increase historical awareness for the younger generation in Solo. This research uses qualitative descriptive methods, so that in answering the formulation of the problem must be done through theoretical and empirical studies. Theoretical studies use literature studies and relevant literature, data obtained in the field, accompanied by data triangulation techniques. This qualitative research analysis process is carried out simultaneously with the data collection process. The value of local tradition wisdom plays an important function for character building in the younger generation, can bring out attitudes that uphold local values and wisdom. The value of local wisdom has the potential to make the younger generation aware of the importance of increasing historical awareness for the realization of unity and unity because they are aware of their role for the Indonesian nation.